Average Daily Risk Range (ADRR) in Young Children With Type 1 Diabetes. (January 2014) - Monaghan, Maureen; Younge, Tamiko B.; McCarter, Robert; Cogen, Fran R.; Streisand, Randi
Objective: The objective was to examine the utility of the average daily risk range (ADRR) in young children with type 1 diabetes. Methods: Self-monitored blood glucose (BG) data and A1c values were collected from 134 children (ages 2-6). Other measures of BG variability and diabetes care were calculated using self-monitored BG data. ADRR, A1c, and other glycemic indices were compared to assess their distinctiveness and utility as measures of BG variability and glycemic control. Results: Of young children's ADRR values, 72% were in the "high-risk" range using adult guidelines. ADRR and A1c were highly correlated with indicators of hyperglycemia but only weakly correlated with measures of hypoglycemia. ADRR was moderately correlated with minimum BG value in the past 30 days but not percentage of BG values below 70 mg/dL. A1c was not correlated with either measure of hypoglycemia. Conclusions: ADRR values confirm the high degree of BG variability present in young children with type 1 diabetes, particularly as compared with adults. New ADRR risk guidelines are needed for pediatric patients. ADRR and A1c are adequate indicators of hyperglycemia in young children. However, both ADRR and A1c failed to effectively capture hypoglycemia risk in this sample, and neither ADRR nor A1c can take the place of review of raw BG data to evaluate BG variability in young children.